2D speckle-tracking echocardiography assessment of left atrial and left ventricular mechanics: outcomes in patients with atrial fibrillation treated with hybrid ablation and left atrial appendage surgical closure - Andrea Maria Paparella; Luigi Pannone; Gianni Pedrizzetti; Giacomo Talevi; Domenico Giovanni Della Rocca; Antonio Sorgente; Rani Kronenberger; Gaetano Paparella; Ingrid Overeinder; Gezim Bala; Alexandre Almorad; Erwin Ströker; et al. (Frontiers in Bioengineering and Biotechnology)
Background and aimsHybrid atrial fibrillation (AF) ablation is a therapeutic option in non-paroxysmal AF. Our study examines cardiac mechanics changes after hybrid AF ablation plus epicardial closure of left atrial appendage (LAA).MethodsAll consecutive patients undergoing hybrid AF ablation at UZ Brussel were evaluated. They received pulmonary vein isolation (PVI), posterior wall isolation (LAPWI), and epicardial LAA closure. Left atrium (LA) and Left ventricle (LV) mechanics were analyzed, with the following measures obtained at baseline, post-ablation, and follow-up: 1) volumes (EDV, ESV); 2) ejection fraction (EF); 3) strain (ENDO GCS, ENDO GLS); 4) forces (LVLF, LVsysLF, LVim, LVs).ResultsA total of 50 patients were included. At follow-up, LAEDV decreased from baseline [44.7 mL vs 53.8 mL, P = 0.025]. LA ENDO GCS and GLS increased post-ablation, with further GLS improvement at follow-up. LV ENDO GCS and LV ENDO GLS also rose post-ablation [-26.7% vs. −22.5%, P < 0.001] and [-20.57% vs. −16.6%, P < 0.001], respectively. LVEF increased post-ablation [54.6% vs 46.3%, P < 0.001]. There was an increase in all LV hemodynamic forces (HDFs) and in particular: LVLF and LVsysLF increased post-ablation [15.5% vs 10.4%, P < 0.001] and [21.5% vs 14.11%, P < 0.001], respectively. LVim also increased post-ablation [19.6% vs 12.8%, P < 0.001]. Finally, there was an increase in LVs post-ablation compared to baseline [10.6% vs 5.4%, P < 0.001].ConclusionIn patients undergoing hybrid AF ablation, there was a significant and persistent improvement in the mechanical and hemodynamic functions of both LA and LV.